2018
DOI: 10.1186/s40425-018-0451-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived exosomal HMGB1 fosters hepatocellular carcinoma immune evasion by promoting TIM-1+ regulatory B cell expansion

Abstract: BackgroundRegulatory B (Breg) cells represent one of the B cell subsets that infiltrate solid tumors and exhibit distinct phenotypes in different tumor microenvironments. However, the phenotype, function and clinical relevance of Breg cells in human hepatocellular carcinoma (HCC) are presently unknown.MethodsFlow cytometry analyses were performed to determine the levels, phenotypes and functions of TIM-1+Breg cells in samples from 51 patients with HCC. Kaplan-Meier plots for overall survival and disease-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(197 citation statements)
references
References 44 publications
6
181
0
Order By: Relevance
“…3CircRNAs act as protein/ peptide translators. CircRNAs are reported to function as translation templates, and they may encode proteins/ peptides involved in tumour pathogenesis and progress [57,58]. 4CircRNAs act as regulators of gene transcription and expression.…”
Section: Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…3CircRNAs act as protein/ peptide translators. CircRNAs are reported to function as translation templates, and they may encode proteins/ peptides involved in tumour pathogenesis and progress [57,58]. 4CircRNAs act as regulators of gene transcription and expression.…”
Section: Circrnasmentioning
confidence: 99%
“…1b). Studies have shown that tumour cell-derived exosomes are involved in multiple immune activities in tumour progression [58,70,71]. In addition, some exosomal RNAs from donor cells, including circRNA, can function in recipient cells [72][73][74].…”
Section: Circrnas Mediate Tumour Immune Surveillancementioning
confidence: 99%
“…TIM-1 + Breg cells create a microenvironment in which IL-10 is secreted and the activity of CD8+ T is impaired, thus favoring HCC progression. These data could be the basis for the development of immunotherapy strategies in HCC [55].…”
Section: Extracellular Vesicles In Hepatocellular Carcinomamentioning
confidence: 89%
“…Few studies have shown that TEXs induce differentiation of naïve B cell to a regulatory phenotype with production of inhibitory cytokines that leads to antitumor immune response inhibition. 147,148 In addition, TEXs could reduce antibody-dependent cell cytotoxicity (ADCC) through interfering with tumor-reactive antibodies binding to tumor cells. 149 In contrast, TEXs were also described to drive antibody production, the underlying mechanism remaining to be explored.…”
Section: B Cellsmentioning
confidence: 99%